Inhibition of Leishmania Major PTR1 Gene Expression by Anti-sense in Escherichia Coli - M Mohebali; F Mahboudi; A Haghighi; M Bandehpour; F Kheirandish; B Kazemi (Tehran University of Medical Sciences, 2012)
Background:Protozoa related to Trypanosome family including Leishmania,synthesize enzymes to escape from drug therapy.One of them is PTR1 that its enzymatic activity is similar to dihydrofolate reductase(DHFR)Dihydrofolate reductase - thymidylate synthase has a major role in DNA synthesis, if it is inhibited, the result would be the death of parasite. Since PTR1 activity is similar to DHFR, causes the decrease of inhibition effect of drug. The aim of this study was inhibition of Iranian L. major PTR1 expression with mRNA antisense in prokaryotic system as an approach to appear of the drugs therapeutic effects more.Methods: PTR1 gene  was ligated to pACYCDuet-1 and pcDNA3 plasmids as sense and antisense plasmids, respectively. Simultaneously transfer of sense and antisense plasmids was done in E.coli strain M15.SDS-PAGE and western blot analysis were carried out to analyze the expression.Results:Sense and antisense plasmids were prepared and confirmed by restriction analysis and PCR then simultaneously transfer of them was done.SDS-PAGE and western blot analysis showed PTR1 gene was inhibited by mRNA antisense in bacterial cells.Conclusion:Expression of PTR1 gene in sense plasmid was inhibited successfully by antisense plasmid.